Iran's Retaliation to Israeli Attack on Iranian Embassy: Wilayat Al-Faqih's Perspective - Ida Susilowati; Mubarok, Sofi; Nurjannah, Siti (The Indonesian Islamic Studies and International Relations Association (Insiera), 2026)
On April 1, 2024, Israel launched an airstrike on the Iranian Embassy in Damascus that killed two senior Quds Force generals and seven members of Iran's Islamic Revolutionary Guard Corps (IRGC). The attack triggered a retaliation from Iran on April 13, 2024. This study aims to analyze Iran's retaliation policy against Israeli attacks from the perspective of Wilayat al-Faqih as the basis of the government system in Iran. The descriptive analytical method based on qualitative research is applied in analyzing Iran's retaliation policy, which uses a literature study technique in data collection. The results of the study show the implications of the Wilayat al-Faqih system in Iran's retaliation policy, which are shown in several points of analysis, namely: Iran's retaliation policy is the policy of the Supreme Leader and President of Iran; Iran's retaliation policy is a form of 'True Promise Operation' which is based on the Wilayat al-Faqih system as a determinant of the direction of Iran's foreign policy; and The existence of socio-political support from countries, such as: Russia, China, North Korea along with several international organizations, such as: Gulf Cooperation Council (GCC) and the European Union which also strengthen the direction of Iran's foreign policy in the context of state defence based on the Wilayatul Faqih system. This study provides insight into how ideology can influence a country's policy in the dynamics of international conflict.